Particle-Size Distribution of Lead and Environmental Risk Assessment in Agricultural Soils Contaminated by Different Smelters - Lei Shi, Shuaixia Liu, Bo Huang, Qiming Zheng, Mengjuan Ma, Xianggang Feng, Yanlin Cheng, Mingze Li (Forest Chemicals Review, 1970)
Soil particle size was an important factor for the transformation of soil heavy metals and environmental risk. However, the impact of soil particle on the allocation, and environmental risk of lead (Pb) in contaminated soil by different smelters was seldom addressed. In the study, five soil particle sizes (0.9-2 mm, 0.3-0.9 mm, 0.15-0.3 mm, 0.075-0.15 mm and <0.075 mm) from the soil polluted by different smelters were separated by the physical method, respectively. The impact of particle size on soil Pb, and ecological risks were investigated by BCR continuous extraction and redundancy analysis. The results showed that soil pH, SOM, CEC and EC increased with the decrease of particle size, except JY soil EC. The reducible Pb content in contaminated soil increased with decreasing particle size. Furthermore, soil Pb had a high accumulation index and potential ecological risk in different soil particle sizes. Therefore, effective measures should be taken to the risk control for agricultural soil contaminated by smelters.